(untitled) (Baghdad Science Journal, 2004)
Hair is an excellent indicator for abnormal concentration of toxic elements , In this study a random samples from girls hair of 12 cm long were irradiated by a flux of neutrons (4x10^ n/ cm^.s) obtained from an Am-Be neutron source of 5-Ci activitity . The y-ray activity measurements were carried out by using a " 5x5 " well- type Nal (Tl) detector. The study indicates clearly that the maximum concentration of elements was at about 7 cm hair length.